The Saint's saints : hagiography and geography in Jerome - Weingarten, Susan. (Ancient Judaism and Early Christianity, 2005)
The Saint's Saints presents Jerome's world picture as seen through his saints' Lives . It analyses both his rhetoric and his descriptions of realia , and the way he combines classical, Christian and Jewish sources to re-write the biblical Holy Land as a new and Christian world for his readers. Susan Weingarten looks at how Jerome dovetails his literary sources with his experience of the material world of the fourth century to write the Lives of the saints Paul, Hilarion, Malchus and Paula, effectively using them to write the Life of Saint Jerome. This is the first full-length study of Jerome's saints' Lives . It widens the on-going debate about mutual influences in Jewish and Christian literature in the fourth century, and revises our picture of the historical geography of Palestine.